OUTSTANDING SHARES AND RETURN ON EQUITY ON STOCK PRICE : AN EVIDENCE OF OIL AND GAS COMPANIES IN INDONESIA STOCK EXCHANGE - Nabut, Bernhard Peter; Sinabutar, Romulo (2021)
Every company that listed want to have a good value of their company. And stock price is one of the important things to consider in assessing the company value. This study examines the effect of outstanding shares and return on equity on stock price. This research is explanatory research with a quantitative approach and conduct using descriptive statistics. The analysis technique used in this research is multiple linear regression. Return on equity has a low positive relationship level and not have a significant effect on the stock price. The outstanding shares studied has a low positive level of relationship. Likewise, the outstanding shares have a significant effect on the stock price. Both, with simultaneous test, return on equity and outstanding shares have a value above the standard so it can be concluded that there is no influence on the stock price.